Diurnal variations in human corneal thickness. Issue 12 (December 1996) - Harper, C L; Boulton, M E; Bennett, D; Marcyniuk, B; Jarvis-Evans, J H; Tullo, A B; Ridgway, A E
Abstract : AIM: To elucidate the diurnal variation in human corneal thickness over a 48 hour period. METHOD: Changes in central corneal thickness were monitored in eight healthy subjects (four male, four female) aged between 10 and 63 years using an ultrasonic pachymeter. Measurements were made over a 48 hour period-immediately before sleep, immediately upon waking and at 15, 30, 45 minutes, 1, 1.5, 2, 2.5, 3 hours, and at 2 hour intervals thereafter throughout the remainder of each day. RESULTS: The mean corneal thickness for the group (SD) was 546 (14) microns, with a mean overnight increase of 5.5% (2.9%) (range 1.9-12.6%) and a maximum diurnal increase of 7.2% (2.8%) (range 2.1-14.3%). Individual differences in the extent of diurnal and overnight variation occurred within the group. For three subjects, the first reading taken on waking was not the highest and corneal thickness continued to increase. CONCLUSION: These data confirm an increase of corneal thickness during sleep, but also reveal considerable variation during waking hours. Thus, the overnight changes in corneal thickness are not truly representative of diurnal variations in human corneal thickness and, in fact, much greater diurnal variation occurs than the 3.0-4.4% previously reported.